ANALYSIS OF THE QUALITY OF SMOKED WHITELIPPED EEL CATFISH IN “MINA MULYA” FISH PROCESSING GROUP, PASIR SAKTI, EASTERN DISTRIC OF LAMPUNG - Novita Mrdiana (The University of Lampung, 2014)
The aimof this researchwas to find out the quality of smoked whitelipped eel catfish in difference smoking timeat “MinaMulya” Fish Processing Group, Pulosari Village, Pasir Sakti, Eastern Distric of Lampung. The reaserchwas conducted infour levels smoking time,which are 1, 2, 3 and 4 hours. The analysis on smokedwhitelipped eelcatfish applied kind of proximate analysis (fat level, protein level,ash level and moisture level), microbiologyanalysis (Total Plate Count (TPC), Escherechia coli bacteria, Salmonella sp. bacteria and Staphylococcus aureusbacteria) and organoleptic analysis (appearance, odour, flavour and texture). The results of this research showthat the smoking time levels affect the quality of whitelipped eel catfish. The proximate analysis result showdifferences among the treatments especially on the proximate analysis. Organoleptic analysis shows that onappearance parameter, only whitelipped eel catfish that are smoked for 3 hours fulfill theminimumvalue (7,0).Whereas organoleptic values for odour, flavour and texture parameter showthat onlywhitelipped eel catfish thatare smoked for 1 hour that does not fulfill theminimum value. Microbiology analysis shows that the content ofTPC and Escherechia coli bacteria smoked fish get under the maximum value of tolerance arrenged on SNI ineach treatment. The content of Salmonella sp. and Staphyococcus aureus bacteria are negative on the wholetreatments.